Raising Awareness Towards Underdiagnosed Renal Hypouricemia: A Case Report - Pedro Lisboa-Gonçalves; Filipa Ferreira; Isabel Tavares; João Paulo Oliveira (Publicações Ciência e Vida, 2023)
Renal hypouricemia (RHUC) is an autosomal recessive disease caused by the dysfunction of uric acid (UA) transporters in the proximal tubule causing increased fractional excretion of uric acid (FEUA). It is associated with mutations of SLC22A12 that codifies for URAT1, involved in RHUC type 1, or SLC2A9 which codifies for GLUT9 and is involved in RHUC type 2. We present the case of a man diagnosed with RHUC type 2 following hospitalization for acute kidney injury (AKI). A 43-year-old was hospitalized due to AKI after a 20 km walk at an outdoor temperature of 30°C. On the objective examination, he was dehydrated. Blood tests presented severe azotemia (creatininemia 16.43 mg/dL, uremia 254 mg/dL), UA 3.6 mg/dL, fosfatemia 6 mg/dL, Na 138 mEq/L, K 4.2 mEq/L, Cl 102 mEq/l, arterial gasometry with pH 7.35, pCO2 36 mmHg, HCO3 20 mmol/L, lactates 1.4 mmol/L. Urine test with proteinuria and unremarkable sediment. His kidneys had foci of microlithiasis. He started vigorous fluid therapy and sustained improvement in renal function was seen, with no need for renal function replacement therapy. The subsequent evaluation showed hypouricemia <1.5 mg/dL and FEUA of 32.5% (normal range 5.5%-8.5%). The molecular study identified the variant c.1221del p.(His407Glnfs*8) in the SLC2A9 gene in homozygosis, which established the diagnosis of RHUC type 2. This case highlights the importance of recognizing hereditary RHUC to prevent its manifestations, including exercise-induced AKI, nephrolithiasis, nephrocalcinosis, and more rarely, progression to stage 5 CKD. Its diagnosis should be considered in individuals with serum UA <2 mg/dL and elevated FEUA. Additionally, it should be confirmed by the identification of mutations in homozygous or compound heterozygous in SLC22A12 or SCL2A9. Treatment includes xanthine oxidoreductase inhibitors and adequacy of physical activity. The use of uricosuric antihypertensive drugs whose mechanism of action involves blocking the URAT1 transporter should be avoided.